RATIONAL DRUG DESIGN OF POTENT V600E-BRAF KINASE INHIBITORS THROUGH MOLECULAR DOCKING SIMULATION - Bello Abdullahi Umar; Adamu Uzairu; Gideion Adamu Shallangwa; Sani Uba (The Journal of Engineering and Exact Sciences)
B-RAF is a one of the RAF protein kinase group that contribute to the development of different types of cancer. V600E-BRAF protein has lot potential for scientific investigation as the therapeutic target owing to its participation in melanoma cancer and is the molecular target of many anticancer compounds like quinolinylaminopyrimidines (QAP) derivatives. In this research, interactions of QAP derivatives with V600E-BRAF kinase were modeled and predicted using molecular docking simulation approach with the help of Autodock vina version 4.0 of Pyrx software. The molecular docking simulation result of this research shows that QAP6 (?11.7 kcalmol-1) best inhibit V600E-BRAF when compared with other QAP analogous within the dataset and was found to be better than the standard V600E-BRAF inhibitor vemurafenib (-11.3 kcalmol-1). This compound (QAP6) were further used in designing novel and potent V600E-BRAF inhibitors by attaching substituents to the quinoline ring of the compound. Moreover, the two newly designed inhibitors N1 and N2 with a binding energy of ?12.7 kcalmol-1 and –12.9 kcalmol-1 respectively were found to be more potent than the parent structure QAP6 (?11.7 kcalmol-1) and the standard V600E-BRAF inhibitor vemurafenib (-11.3 kcalmol-1). Thus; this study provides a valuable approach and new direction to novel drug discovery. There is hope in the future studies to include the synthesis and evaluation of these newly designed inhibitors which can establish them to be the most potent V600E-BRAF inhibitors and efficient ant-melanoma cancer drug.